The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5mb00237k
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics identifies the intersection of phosphoethanolamine with menaquinone-triggered apoptosis in an in vitro model of leukemia

Abstract: Altered metabolism is increasingly acknowledged as an important aspect of cancer, and thus serves as a potentially fertile area for the identification of therapeutic targets or leads. Our recent work using transcriptional data to predict metabolite levels in cancer cells led to preliminary evidence of the antiproliferative role of menaquinone (Vitamin K2) in the Jurkat cell line model of acute lymphoblastic leukemia. However, nothing is known about the direct metabolic impacts of menaquinone in cancer, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
0
21
0
3
Order By: Relevance
“…PhosE exhibits antitumor activity in various in vitro and in vivo models by affecting multiple signaling pathways (9–15). Interestingly, vitamin K2-induced apoptosis in Jurkat cells is ascribed to intracellular PhosE accumulation (18). …”
Section: Introductionmentioning
confidence: 99%
“…PhosE exhibits antitumor activity in various in vitro and in vivo models by affecting multiple signaling pathways (9–15). Interestingly, vitamin K2-induced apoptosis in Jurkat cells is ascribed to intracellular PhosE accumulation (18). …”
Section: Introductionmentioning
confidence: 99%
“…Other work showed that menaquinone can have therapeutic effects on prostate cancer cells, whether or not they were hormone-dependent, via caspase-3 and -8 dependent apoptosis [45]. Interestingly, recent metabolite profiling-driven work identified an unknown connection between menaquinone and phosphoethanolamine in the induction of apoptosis in a leukemic cell line [46]. This is particularly relevant given a recent series of papers showing the anti-cancer effects of phosphoethanolamine on breast cancer, leukemia, and renal cell carcinoma [47][48][49].…”
Section: Endogenous Metabolites and Antimetabolites To Control Cancermentioning
confidence: 99%
“…A capacidade da FO-S em promover apoptose, em diferenças linhagens de células tumorais, tem sido demostrada em diversos estudos publicados (Ferreira et al, 2011;Ferreira et al, 2012a;Ferreira et al, 2012b;Ferreira et al, 2013b;Ferreira et al, 2013c;Luna et al, 2014;Luna et al, 2016). Interessantemente, a apoptose desencadeada pela vitamina K2, em células de leucemia aguda humana Jurkat, foi atribuída ao acumulado intracelular de fosfoetanolamina (Dhakshinamoorthy et al, 2015).…”
Section: Discussionunclassified
“…A internalização do TRAIL e seus receptores pode recrutar fatores que induzem a permeabilização da membrana lisossomal, resultando na liberação da catepsina B para o citosol Guicciardi, 2014 A análise morfológica por MEV, das células tumorais B16F10 tratadas com os lipossomas DODAC/FO-S, evidenciou que as células morrem após a ativação de mecanismos pró-apoptóticos, conforme discutido anteriormente e relatado nas publicações com a FO-S (Ferreira et al, 2011;Ferreira et al, 2012a;Ferreira et al, 2012b;Ferreira et al, 2013b;Ferreira et al, 2013c;Luna et al, 2014;Dhakshinamoorthy et al, 2015;Luna et al, 2016). Diversos trabalhos descrevem as alterações que ocorrem nas células apoptóticas, como a formação de bolhas na membrana, seguida por cariorrexia, e a separação de fragmentos de células em corpos apoptóticos, durante um processo chamado "budding" (Elmore, 2007;Goldar et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation